Omalus biaccinctus - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
4. Omalus biaccinctus (Buysson, 1892) Ellampus biaccinctus Buysson in André 1892: 152. Syntypes ♂, ♀; France (MNHN) (examined). Omalus biaccinctus : Linsenmaier 1959: 18, Valkeila 1962: 63, Erlandsson 1971: 88, Banaszak 1980: 10, Silfverberg 1981: 61, Vikberg 1986b: 67, Cederberg 2000: 177, Söderman & Vikberg 2003: 44, Soon 2004: 19, 45, Cederberg 2005: 290, Sörensson 2008f, Allearter.dk 2010, Orlovskytė et al. 2010: 153, Paukkunen 2010: 542, Rosa & Soon 2012, Dyntaxa 2013. Material examined. Denmark: LFM : Kaerstrup, 1913, 1 ♀; Søholt, 1917, 1 ♀; * Latvia: Dalbe, 22.VI.1973, 1 ♀ (V. Tumšs); Langstini, 25.VII.1971, 1 ♀ (V. Tumšs); Upseims, 16.VII.1974, 1 ♀ (V. Tumšs); * Norway: BØ : Hole, Utstranda, 25.VI–2.VIII.2011, 2 exx. (F. Ødegaard); Ø : Hvaler, Asmaløy, 25.VI.2010, 1 ex. (F. Ødegaard); *Russian Fennoscandia: Ik : Metsäpirtti [= Zaporozhskoe], 12.VII.1934, 1 ♀ (A. Merisuo). Distribution. Denmark, Estonia, Finland, * Latvia, * Norway, Sweden, *Russian Fennoscandia.—Westpalearctic: from West Europe to West Asia (Linsenmaier 1959). Most common in the Mediterranean area (Mingo 1994). Remarks. Omalus biaccinctus is a rare species in the Nordic and Baltic countries. It has not yet been recorded in Lithuania. The species has been classified as vulnerable in Finland (Paukkunen 2010). In Sweden it is also uncommon, but was excluded from the latest national red list (Cederberg et al. 2010). The Latvian specimens were found in LMSZ in Riga, where they had been erroneously identified as O. aeneus by Tumšs. Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on pages 9-10, DOI:10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433